DEVELOPMENT OF FIRE ENGINE NAVIGATION SYSTEM AND FIRE HYDRANT WATER FLOW RATE - AHMAD, MOHD SHAFARIZ AKMAL (Universiti Teknologi PETRONAS, 2017)
This project title Development of Engine Navigation System and Fire Hydrants locator is about mapping fire hydrants location, calculate distance between fire hydrants then display in Hydrant tracker. This project will add pressure sensor to calculate water flow in pipeline that connected with fire hydrants. The author adds water level measurement sensor on top of public water tank, because there are correlation water level measurements with water flow rate. Mapping fire hydrants critical task because the author needs to know the exact GPS coordinates. Fire fighters need quick action hence by using virtual mapping system will help fire fighters.